2001
DOI: 10.1016/s0735-1097(01)01115-9
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection and evaluation of atherosclerotic coronary plaques with multislice computed tomography11This study was performed without additional financial support.

Abstract: Our results indicate that coronary lesion configuration might be correctly differentiated by MSCT. Since also rupture-prone soft plaques can be detected by MSCT, this noninvasive method might become an important diagnostic tool for risk stratification in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
351
3
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(386 citation statements)
references
References 26 publications
14
351
3
18
Order By: Relevance
“…14 In a study by Schröder et al, 15 soft, intermediate, and calcified plaques in the coronary arteries as defined by IVUS had a unique density, detected by contrast-enhanced MD-CTA (14Ϯ26 HU for soft plaques, 91Ϯ21 HU for intermediate plaques, and 419Ϯ194 HU for calcified plaques). 15 In a preliminary study of heart specimen, we found that lipid-rich plaques had low density (50Ϯ12 HU), whereas fibrous plaques presented with higher density (89Ϯ31 HU) (Figures 1 and 2). 16 Similar findings have been reported in carotid artery plaques.…”
Section: Multidetector-row Ct For Coronary Calciummentioning
confidence: 97%
“…14 In a study by Schröder et al, 15 soft, intermediate, and calcified plaques in the coronary arteries as defined by IVUS had a unique density, detected by contrast-enhanced MD-CTA (14Ϯ26 HU for soft plaques, 91Ϯ21 HU for intermediate plaques, and 419Ϯ194 HU for calcified plaques). 15 In a preliminary study of heart specimen, we found that lipid-rich plaques had low density (50Ϯ12 HU), whereas fibrous plaques presented with higher density (89Ϯ31 HU) (Figures 1 and 2). 16 Similar findings have been reported in carotid artery plaques.…”
Section: Multidetector-row Ct For Coronary Calciummentioning
confidence: 97%
“…We characterized plaque morphology on axial scans with confirmation of our findings on MPR, MIP, VR, and SSD images. Using internal classification criteria, we studied different plaque types by using axial scans, and we divided them into 3 different groups according to Schroeder et al 35 : 1) fatty plaques (attenuation Ͻ50 HU); 2) mixed plaque (attenuation between 50 and 119 HU); and 3) calcified plaques (attenuation Ͼ120 HU). The attenuation was measured in Hounsfield units with the use of a circular or elliptical region of interest cursor in the predominant area of plaque at each level.…”
Section: Image Analysismentioning
confidence: 99%
“…Addition of multiple detectors and improved temporal and spatial resolution on current CT scanners allow for reliable, non-invasive detection and characterization of coronary plaques. [17][18][19][20][21][22][23] Early CT scanners using either 4 or 8 rows of detectors were able to provide accurate data on proximal coronary trunks, while newer generation scanners demonstrate reliable visualization of all coronary segments including distal branches. 23 …”
Section: Ct Angiographymentioning
confidence: 99%